Post - Coital Vaginal Evisceration Following 8 Years in a Patient was Operated for Endometrium Cancer: Report of a Case and Review of the Literature - Okyay, Emre; Saatli, Bahadır; Bodur, Taylan; Pala, Gürsoy; Çağlayan, Erkan; Gülekli, Bülent (Gynecology Obstetrics & Reproductive Medicine, 2012)
Intestinal prolapse through vagina following hysterectomy secondary coitus is rare. It is generally seen in postmenopausal women after vaginal hysterectomy or multiple surgeries performed for pelvic floor disorders. However, in English literature, there are only a few cases of vaginal evisceration after radical hysterectomy and pelvic lymphadenectomy, but all of these cases were cervical cancer. We report a case of a 49-year old woman presenting with evisceration of the small bowel from the vagina eight years after total abdominal hysterectomy (TAH), bilateral salpingoopherectomy (BSO) and pelvic-paraaortic lymphadenectomy for stage Ib endometrioid type endometrial cancer.